Soft power, culture and modernity: Responses to Bollywood films in Thailand and the Philippines. (August 2019) - Athique, Adrian
India's official embrace of the soft power concept and the popular equation of Bollywood films with India's international image are discussed here with reference to their contemporary convergence. This article seeks to make the case that the underlying claims of the soft power doctrine necessitate an empirical test at the level of grassroots reception. Further, this article also seeks to shift the emphasis from 'impressing the West' towards interrogating the dynamics of India's cultural diplomacy in other Asian states. With these aims in mind, this article presents two qualitative case studies from Chiang Mai, Thailand and Metro Manila in the Philippines. The responses collected indicate the inherent complexities of Inter-Asian dialogues on culture and modernity as well as the importance of the local media environment in determining perceptions of contemporary India. Ultimately, the capacity of popular culture to create a positive impression and to counter existing prejudices and misconceptions is supported in a series of reception studies. At the same time, the 'moral superiority' and historical legacies that are assumed to underpin India's cultural prestige in the region are challenged by the content and tone of these responses from the general public. In the contemporary setting of Association of South East Asian Nations (ASEAN), it becomes clear that the mediation of Indian culture operates within an increasingly transnational media environment and a competitive modernity that informs comparative perspectives between Asian cultures.